Sewage Sludge Use on Agricultural Land - Eberle, William M.; Whitney, David A.; Powell, G. Morgan (My University, 1994)
This publication describes how to use sewage sludge on agricultural land.
MF1168_1994_09
Keywords: MF1168; Health and Safety; Environment and Natural Resources; MF